Kill Bill. Volume 2 [videorecording (DVD)] - Tarantino, Quentin; Thurman, Uma; Carradine, David; Madsen, Michael; Hannah, Daryl; Parks, Michael, 1940-2017 (Miramax Home Entertainment ; Distributed by Buena Vista Home Entertainment, 2004)
The Bride continues on her deadly pursuit of her former partners in the Deadly Viper Assassination Squad, who, in a furious assault, attempted to murder her and her unborn child on her wedding day. As the Bride faces off against allies-turned-nemeses Budd and Elle, she flashes back to the day of her deadly wedding. We learn how she was recruited and trained and about her relationship with Squad leader Bill.